2007
DOI: 10.1016/j.biopsych.2006.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyl Transferase and Expression of Schizophrenia in 73 Adults with 22q11 Deletion Syndrome

Abstract: Background-Catechol-O-methyl transferase (COMT) is a candidate gene for schizophrenia with a role in dopamine metabolism, particularly in frontal cortex. COMT is within the region commonly deleted in 22q11 deletion syndrome (22q11DS), a syndrome with high prevalence of schizophrenia. We examined the role of COMT in schizophrenia-related expression in 22q11DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 40 publications
6
84
3
2
Order By: Relevance
“…All studies need replication. found that the lower-activity Met allele was not significantly more prevalent than the Val allele in 33 patients with schizophrenia [36], which was consistent with other studies with fewer affected patients [7,19]. Met COMT hemizygosity is present in about one half of patients with 22qDS (with and without psychotic illness) [36].…”
Section: Linkage and Association Studiessupporting
confidence: 90%
See 4 more Smart Citations
“…All studies need replication. found that the lower-activity Met allele was not significantly more prevalent than the Val allele in 33 patients with schizophrenia [36], which was consistent with other studies with fewer affected patients [7,19]. Met COMT hemizygosity is present in about one half of patients with 22qDS (with and without psychotic illness) [36].…”
Section: Linkage and Association Studiessupporting
confidence: 90%
“…found that the lower-activity Met allele was not significantly more prevalent than the Val allele in 33 patients with schizophrenia [36], which was consistent with other studies with fewer affected patients [7,19]. Met COMT hemizygosity is present in about one half of patients with 22qDS (with and without psychotic illness) [36]. Several studies have found no significant differences between Met and Val allele carriers in positive and negative symptom severity [7,36,37].…”
Section: Linkage and Association Studiessupporting
confidence: 87%
See 3 more Smart Citations